2023
DOI: 10.1002/adhm.202301724
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Structural Protein Based Magnetic Responsive Scaffold for Enhancing Bone Regeneration by Physical Stimulation on Intracellular Calcium Homeostasis

Hai‐Feng Liang,
Yan‐Pei Zou,
An‐Nan Hu
et al.

Abstract: Bone matrix has distinct architecture and biochemistry which present a barrier on synthesizing bone‐mimetic regenerative scaffolds. To mimic the natural structures and components of bone, we prepared the biomimetic structural decellularized extracellular matrix (ECM)/regenerated silk fibroin (RSF) scaffolds incorporated with magnetic nanoparticles (MNP) using a facile synthetic methodology. The ECM/RSF/MNP scaffold is hierarchically organized and interconnected porous structure with silk fibroin twined on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Magnetic and electric fields are currently being explored for controlled drug delivery strategies. As for magnetic field, it is reported that an external static magnetic field with magnetic responsive scaffolds incorporated with magnetic nanoparticles effectively promotes osteogenic differentiation and neogenesis of endotheliocytes in vitro and in vivo [ 259 ]. As for electromagnetic field, it is reported that an external magnetic field force conduct on the core of material increase charge density on the shell and finally increase the membrane surface potential, hence activates osteogenesis and bone regeneration [ 260 ].…”
Section: Future Perspectives For Enhancing Oral-maxillofacial Repair ...mentioning
confidence: 99%
“…Magnetic and electric fields are currently being explored for controlled drug delivery strategies. As for magnetic field, it is reported that an external static magnetic field with magnetic responsive scaffolds incorporated with magnetic nanoparticles effectively promotes osteogenic differentiation and neogenesis of endotheliocytes in vitro and in vivo [ 259 ]. As for electromagnetic field, it is reported that an external magnetic field force conduct on the core of material increase charge density on the shell and finally increase the membrane surface potential, hence activates osteogenesis and bone regeneration [ 260 ].…”
Section: Future Perspectives For Enhancing Oral-maxillofacial Repair ...mentioning
confidence: 99%